2018
DOI: 10.1007/s10775-018-9375-4
|View full text |Cite
|
Sign up to set email alerts
|

Nordic research on educational and vocational guidance: a systematic literature review of thematic features between 2003 and 2016

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
10
0
4
Order By: Relevance
“…A recent article (Haug et al, 2019b) argues that the understanding of career guidance found in the research literature from the Nordic countries between 2003 and 2016 broadly coincides with the definition of educational and vocational guidance stated in the European Lifelong Guidance Policy Network (ELGPN) Glossary (2014). There, educational guidance is defined as 'helping an individual to reflect on personal educational issues and experiences and to make appropriate educational choices', and vocational guidance is defined as 'help for individuals to make choices about education, training and employment' (ELGPN, 2014).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…A recent article (Haug et al, 2019b) argues that the understanding of career guidance found in the research literature from the Nordic countries between 2003 and 2016 broadly coincides with the definition of educational and vocational guidance stated in the European Lifelong Guidance Policy Network (ELGPN) Glossary (2014). There, educational guidance is defined as 'helping an individual to reflect on personal educational issues and experiences and to make appropriate educational choices', and vocational guidance is defined as 'help for individuals to make choices about education, training and employment' (ELGPN, 2014).…”
mentioning
confidence: 83%
“…The balance between studies in guidance based on sociology, psychology, and even ethnology and philosophy varies according to the research focus and tradition of each of the Nordic countries (e.g. Haug et al, 2019b;Plant, 2003).…”
Section: Defining Career Guidancementioning
confidence: 99%
“…The participants were asked to talk about quality in career guidance in general and not assess a specific program or a service. This was an important feature of the interviews, the aim of the interviews therefore being to access their understanding of quality in career guidance rather than their retrospective evaluation of a service, which is a common approach in Norwegian school career guidance research (Haug et al, 2019b). My objective was to go deeper into the understandings of quality that inform retrospective evaluations.…”
Section: Career Guidance Quality Articulation In the Norwegian Schoolmentioning
confidence: 99%
“…Регіональні центри профорієнтації сприяють забез печенню комфортного переходу молоді від освіти до ринку праці, і навпаки. З січня 2011 року у Данії працює інтернет платформа електронної профорієнтації eGuidance [13], яка цілодобово за допомогою різнома нітних віртуальних каналів зв'язку (електронної пошти, чату, вебінару, соціальної мережі, телефону або тексто вого повідомлення) сім днів на тиждень надає індиві дуальні послуги з профорієнтації для різних вікових груп населення. Крім інтернет платформи eGuidance, діє національний портал з профорієнтації: www.ug.dk, який допомагає громадянам знаходити актуальну інформа цію про розвиток ринку праці та приймати кваліфіко вані рішення щодо здобуття освіти, навчання та кар'є ри.…”
Section: виклад основного матеріалу з повним обгрунтуванням отриманихunclassified